Optimize Financial Technology, Financial Literacy, and Financial Inclusion in Increasing MSMEs Growth Post Covid19? - Chairul Adhim; Muh. Syahru Ramadhan; Yeye Suhaety (East Asian Journal of Multidisciplinary Research, 2023)
This research seeks to identify optimal technology, financial literacy, and financial inclusion to increase MSME financial growth after COVID-19. The research method uses multiple linear regression tests. The sample in this study was made up of SMEs in West Nusa Tenggara Province using a purposive sampling method. The results of the study show that financial technology, financial literacy, and financial inclusion have an effect on the growth of MSMEs. And the results of the determination coefficient test show that the coefficient of determination is 0.548. This means that 54.8% of the dependent variable can be explained by the independent variables. This shows that 45.2% of the variables are influenced by variables other than those used in this study.